Safety level assessment at selected Malaysian Schools / Paveethra Thegarathah - Paveethra, Thegarathah (2017)
Occupational safety and health management system is a system which is implemented based on a set of regulation. OSHA 1994 is being implemented in the industries and other organizations in Malaysia. The main aim is create a safe working environment. Therefore, safety audit was chosen as a tool to study the level occupational safety and health compliance level at selected Malaysian schools. Two different schools were chosen to compare the compliance level and appropriate safety and health measures were suggested. An audit checklist was used to recognize the possible issues in the chosen safety aspects which are; medical record and exposure, signage and labels, alarm system and evacuation, indoor air quality, safety measures for falling from height, occupational injury and illness reporting and traffic safety. The percentage of compliance was calculated for each aspect. The results obtained shows that School B has a better compliance standard as compared to School A. However, medical records and exposure and occupational injury and illness reporting has scored below 40%. Therefore, all the stakeholders have to cooperate in order to implement a productive safety culture at Malaysian schools.